A Note on Inverse Systems of $\boldsymbol{S(n)}$-Closed Spaces - Lončar, Ivan (Sarajevo Journal of Mathematics, 2015)
The aim of this paper is to study inverse systems of the $S(n)$-closed spaces which are the generalization of H-closed and Urysohn-closed spaces. 2010 Mathematics Subject Classification. Primary: 54A05, Secondary: 54B35